Heat transfer and air movement behaviour in a double-skin façade - Darkwa, J.; Li, Y.; Chow, D.H.C. (Elsevier, 2014)
Theoretical and practical evaluation of a naturally ventilated double skin façade has been undertaken. The study has shown that the double skin façade (DSF) system is capable of supplying adequate ventilation to various levels with little or no additional heating during winter thus saving the bulk percentage of the heating load on the building. However there was an element of overheating in the DSF which may have contributed to an additional cooling load on the building. Even though the operational strategy of mixing return air with trapped air in the cavity helped to minimise the overheating effect, there was still some considerable level of temperature increase in the DSF. Effective thermal management control strategies and systems are therefore encouraged in the design and operation of DSFs.